Social distancing behavior during COVID-19: a TPB perspective. Issue 6 (1st June 2021) - Ang, Tyson; Wei, Shuqin; Arli, Denni
Abstract : Purpose: In responding to the Coronavirus (COVID-19) pandemic, drastic public health measures such as social distancing and lockdowns have been implemented across the globe to slow the spread of the virus. In the USA, the public's reaction to social distancing has been mixed, evident in a high number of people flocking to beaches, bars and shops as coronavirus cases soar. Public health officials have issued strong warnings about the danger people face but the problem persists. To fill this gap, informed by the theory of planned behavior (TPB), this research explores why many people refuse to practice social distancing. Design/methodology/approach: Two studies were conducted during the ongoing COVID-19 pandemic. In the first study, a sample of 750 respondents was recruited from a US online consumer panel to complete a structured survey questionnaire. The data were analyzed using confirmatory factor analysis and structural equation modeling. In the second study, an open-ended questionnaire was administered to 50 US online participants to further uncover people's in-depth perceptions and perspectives toward the pandemic and social distancing. Thematic analysis was used to analyze the data. Findings: The results from the first study show that risk-taking attitude, authoritarianism and subjective norm are significant predictors of social distancing intention and behavior, through perceived severity of COVID-19. Four themes emerged from the second study, which are consistent with the proposed conceptual framework in the first study. Originality/value: Theoretically, the authors' findings first contribute to the emerging marketing literature that focuses on creating sustained positive changes and improving the well-being of consumers, communities and societies. Secondly, their findings corroborate with previous findings documented in the social influence literature by showing that during the times of uncertainty and confusion such as COVID-19, social norms (not forced by laws and regulations) play the most critical role in influencing a voluntary, socially beneficial behavior (such as social distancing). Third, this study extends the application of the TPB into the realm of social distancing behavior. The three main components of the TPB, namely attitude, behavioral control and subjective norm, are shown to predict social distancing behavior. Practically, the results of this research have important implications for public health policies on how to encourage positive public health behavior amid pandemics such as COVID-19.